Peningkatan Kemampuan Pustakawan Perguruan Tinggi pada Masa Pandemi Covid-19 - Novandi, Bima Rahma; Rachman, Margareta Aulia (UI Scholars Hub, 2023)
The ability of librarians who have developed during the pandemic and continue to be utilized in the post-pandemic period that adapts to circumstances is urgently needed. Librarians must strive to improve their capabilities with innovation in various services. This study aims to identify how to increase the ability of UI Librarians during a pandemic. The research approach in this study was qualitative with data collection methods namely interviews, observation, and document analysis. The results of the study showed that during the pandemic, librarians at the UI Library had new abilities both in librarianship and outside of librarianship. These capabilities include increasing ability to process data, improving communication skills, online teaching skills, creating content on social media, repairing website servers, and other capabilities outside the librarianship field. Apart from that, what is interesting about the ability of librarians at the UI Library during a pandemic is the ability to adapt to information technology. This is as a result of the pandemic which has temporarily closed work and services in the library.